Radionuclides proportion and radiological risk assessment of soil samples collected in Covenant University, Ota, Ogun State Nigeria - Adewoyin, O.O.; Omeje, M.; Joel, E.S.; Akinwumi, S.A.; Ehi-Eromoseled, C.O.; Embong, Zaidi (ScienceDirect, 2018)
The activity levels of 238U, 232Th and 40K in soil surrounding major office complexes in Covenant University were analyzed for radiological hazards to determine the safety of the residents in such environment. Sixteen (16) soil samples were collected, prepared and sent to Acme laboratory in Canada for analysis with the use of high purity germanium detector. The mean activity concentrations of 238U, 232Th and 40K were found to be 45?±?10, 135?±?8 and 195?±?20 respectively. The concentrations of 238U and 232Th were found to be higher than the world recommended standard of 35 and 30, while the result for 40K was noted to be lower than the world safe limit. The average values of Raeq, D, AED, Iyr, Hex and ELCR in this study were estimated to be 252.33?Bq/kg, 110.15 nGy/h, 0.13 mSv/y, 1.78, 0.68 and 0.47?×?10-3 respectively. It was noticed that none of the measured parameters was higher than the internationally recommended safe limits. 232Th was found to be the major contributor to the environmental radionuclides in the area of study. Therefore, the inhabitants of the office complexes whose environment was assessed are considered not be exposed to any radiological hazards.